SolarVision Almería: Meteorological measurements - Yann Fabel; Niklas Blum; Bijan Nouri; Stefan Wilbert; Sergio Gonzalez Rodriguez; Luis Zarzalejo (PANGAEA, 2025)
This dataset provides ground-based image and sensor measurement data from a scientific research site in southern Spain (Tabernas, Almería). Its main contributions include all-sky images in the visible spectrum from three different fish-eye cameras capturing clouds motions, as well as diffuse, direct and global solar irradiance measurements from ISO 9060 class A spectrally flat pyrano- and pyrheliometers. The cameras and irradiance measuring devices are co-located within a radius of 20m at the same meteorological station. This dataset contains radiation measurements and additionally meteorological measurements from nearby meteorological stations (within 500m), including ambient temperature, atmospheric pressure, wind speed and direction, and relative humidity. In total, the dataset spans two years, covering August 2022 to July 2024, with measurements recorded at a 1-min resolution during daytime (solar elevation angle exceeding 5°).
In: Fabel, Y et al. (2025): SolarVision Almería: A Ground-Based Dataset of All-Sky Images, Solar Irradiance, and Meteorological Measurements [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.980067